2011
DOI: 10.1308/147870811x566376
|View full text |Cite
|
Sign up to set email alerts
|

The value of intraoperative ultrasound and preoperative imaging, individually and in combination, in liver resection for metastatic colorectal cancer

Abstract: INTRODUCTION Liver resection is proved to offer potential long-term survival for colorectal liver metastases (CRLM). Accurate radiological assessment is vital to enable an appropriate surgical approach. The role of intraoperative ultrasound (IOUS) has been controversial. This study was designed to analyse the accuracy of IOUS compared with that of preoperative imaging (POI) in these patients. MATERIALS AND METHODS A prospective analysis of 51 consecutive patients who underwent liver resection for CRLM was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In patients treated with neoadjuvant chemotherapy, magnetic resonance imaging measurements of steatosis show the highest correlation coefficient and the best diagnostic accuracy, as compared to computed tomography ones (Marsman et al, 2011). Intraoperative ultrasound and preoperative imaging significantly increase the diagnostic accuracy of patients undergoing liver resection for colorectal liver metastases (Lordan et al, 2011). Metachronous resections have a better outcome than synchronous.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated with neoadjuvant chemotherapy, magnetic resonance imaging measurements of steatosis show the highest correlation coefficient and the best diagnostic accuracy, as compared to computed tomography ones (Marsman et al, 2011). Intraoperative ultrasound and preoperative imaging significantly increase the diagnostic accuracy of patients undergoing liver resection for colorectal liver metastases (Lordan et al, 2011). Metachronous resections have a better outcome than synchronous.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, the technique of intraoperative ultrasound (IOUS) was established and since that time has been further refined [17][18][19]. The literature includes studies with a wide range of sensitivities of IOUS (61-92 %) [18,[20][21][22].…”
Section: Intraoperative Ultrasoundmentioning
confidence: 99%
“…In the 1980s, the technique of intraoperative ultrasound (IOUS) was established and since that time has been further refined [17][18][19]. The literature includes studies with a wide range of sensitivities of IOUS (61-92 %) [18,[20][21][22]. Despite this variability, most studies have suggested that the addition of IOUS to preoperative cross-sectional imaging can allow for identification of additional foci of CRLM, and therefore, including this tool in surgical planning has been recommended [18,20,23].…”
Section: Intraoperative Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, intraoperative ultrasonography (IOUS) provides high-resolution imaging and is frequently used for intraoperative decision making. The reported sensitivity of IOUS ranged from 85% to 95% [26][27] . However, the performance of US and IOUS are dependent on the operator's experience, lesion size, location, and echogenicity of the lesions.…”
Section: Introductionmentioning
confidence: 99%